Body fluid status, plasma volume change and its relationship to physical effort during a multistage professional road cycling race - Giorgi, A.; Sanders, D.; Vicini, M.; Lukaski, H.; Gatterer, H. (International Journal of Performance Analysis in Sport, 2018)
Multistage cycling races are very demanding and may profoundly affect the body`s fluid homeostasis. This study aimed at monitoring body fluid volume and plasma volume (PV) changes during multi-stage cycling and to investigate whether changes are associated to work output and perceived exertion during the competition. During the Tour of the Alps cycling stage race 2017 daily hematocrit and hemoglobin evaluations, body weight, bioimpedance, RPE and power output measurements were performed on eight professional road cyclists. Results show modest to large changes in bioimpedance and blood hematocrit values during the race. Work accomplished during stage one was related to changes in vector length and body weight (n = 6, r = 0.821, p = 0.045 and r = ?0.852, p = 0.031, respectively). Additionally, PV changes were associated with vector length changes (r = ?0.759, p = 0.029). During the last stage, PV changes were related to reactance (Xc/H) changes (r = ?0.716, p = 0.046). The physical work performed during the first stage seems to strongly influence fluid volumes, which on the other hand showed some associations to PV changes. These associations were not evident during the following stages but instead a relationship between Xc/h and PV changes occurred, possible indicating fluid shifts. Bioimpedance thus could be a useful tool to identify fluids shift during such competitions.